Confirmation of Calamagrostis salina in China, previously misidentified as C. macilenta, and notes about C. kokonorica and C. macilenta (Poaceae, Agrostidinae) - Paszko, Beata; Chen, Wen-Li; Liu, Bing (Phytotaxa, 2016)
New data on the taxonomy and distribution of three Calamagrostis (including Euroasian Deyeuxia) species (C. kokonorica, C. macilenta, and C. salina) in northwestern and northern China are discussed. Studies were undertaken on the morphological characters to establish relatedness or not of species, and identify characters of diagnostic importance. Chinese herbarium specimens of C. salina previously have been misidentified as Deyeuxia macilenta (= C. macilenta). All available for study Chinese specimens referred to this species should be identified as C. salina. Calamagrostis salina significantly differs from C. kokonorica and C. macilenta by the palea length, relative lengths of palea and lemma, and anther length. Calamagrostis salina is confirmed for Xinjiang, and reported for the first time from Gansu, Nei Mongol and Qinghai. Calamagrostis kokonorica is confirmed for Gansu and Qinghai. The presence of C. macilenta in China is in need of further confirmation. A revised key for C. salina and related species are provided. The descriptions of all taxa are accompanied by information on their geographical distribution in China and adjacent countries.